2017
DOI: 10.3390/ijms18010104
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Foundations of Therapeutic Efficacy and Adverse Events of Statins

Abstract: Background: In the era of precision medicine, more attention is paid to the search for predictive markers of treatment efficacy and tolerability. Statins are one of the classes of drugs that could benefit from this approach because of their wide use and their incidence of adverse events. Methods: Literature from PubMed databases and bibliography from retrieved publications have been analyzed according to terms such as statins, pharmacogenetics, epigenetics, toxicity and drug–drug interaction, among others. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 166 publications
(197 reference statements)
0
14
0
1
Order By: Relevance
“…Decreased cholesterol level in the liver leads to an upregulation of LDL receptors which leads to a decrease in plasma LDL cholesterol[29]. In addition to the decrease in LDL cholesterol, statins lower the level of TG and increase the level of HDL-cholesterol[30].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased cholesterol level in the liver leads to an upregulation of LDL receptors which leads to a decrease in plasma LDL cholesterol[29]. In addition to the decrease in LDL cholesterol, statins lower the level of TG and increase the level of HDL-cholesterol[30].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Statins also have pleiotropic effects and have been shown reduction of hsCRP and other markers of inflammation that help to stabilize plaque, improve endothelial function and decrease vascular inflammation and oxidative stress[30,31]. Statins are divided into high-intensity (atorvastatin 40-80 mg, rosuvastatin 20-40 mg) which can decrease LDL- C by approximately 50% or more; moderate-intensity (Atorvastatin 10-20 mg, rosuvastatin 5-10 mg, simvastatin 20-40 mg, pravastatin 40 mg, lovastatin 40 mg, Fluvastatin 80 mg, pitavastatin 2-4 mg) which can decrease LDL-C by approximately 30%-50% ; and low-intensity (Simvastatin 10mg, Pravastatin 10-20 mg, Lovastatin 20 mg, Fluvastatin 20-40 mg, Pitavastatin 1 mg) which decrease LDL-C by < 30%[19,22].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Therefore, we cannot determine exactly why standard statins could not be switched to strong statins in these patients, but we might reasonably assume the reason is statin intolerance, i.e., the status in which an adequate dose of statin cannot be continuously used because of adverse effects [5,6]. The major reasons for statin intolerance have been reported to be statin-associated muscle symptoms (SAMS) and increased CK levels and their temporal association with initiation of statin therapy [28], partially due to solute carrier organic anion transporter family member 1B1 (SLCO1B1) variant alleles [29]. Nagar et al reported that statin intolerance was observed in approximately 10% in Japanese patients with high CAD risk [5].…”
Section: Discussionmentioning
confidence: 99%
“…Another major risk factor of CVDs is raised blood Chol, which has led to the development of a group of drugs used to lower Chol and triglycerides in patients with elevated Chol. Subsequently, a plethora of studies have been carried out on 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase inhibitors, the so-called statins (reviewed in [209]). Statins block the Chol synthetic pathway in the liver and indeed, these therapies promote a regression and/or delay in the progression of atheromatous plaques.…”
Section: Protein-lipid Interactions In Cardiovascular Diseases (Cvds)mentioning
confidence: 99%